1974
DOI: 10.1126/science.185.4157.1167
|View full text |Cite
|
Sign up to set email alerts
|

Methane Production in the Interstitial Waters of Sulfate-Depleted Marine Sediments

Abstract: Methane in the interstitial waters of anoxic Long Island Sound sediments does not reach appreciable concentrations until about 90 percent of seawater sulfate is removed by sulfate-reducing bacteria. This is in agreement with laboratory studies of anoxic marine sediments sealed in jars, which indicate that methane production does not occur until dissolved sulfate is totally exhausted. Upward diffusion of methane or its production in sulfate-free microenvironments, or both, can explain the observed coexistence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
228
0
3

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(241 citation statements)
references
References 13 publications
8
228
0
3
Order By: Relevance
“…In open oceans, CH 4 sources in shallow water depths are provided by microbial subsurface CH 4 generation taking place in zooplankton guts, the oxygen-deficient interior of particles, or under phosphate-limiting conditions (Karl et al, 2008;Damm et al, 2010). In waters overlying continental shelves, however, the organic-rich sediment serves as a major source of CH 4 in the water column compared to net production in the mixed layer (Martens and Berner, 1974;Martens and Klump, 1980;Reeburgh, 2007). The shallow-water [CH 4 ] can also be elevated due to gas seepages and/or oil spills (Bernard et al, 1976;Reed and Kaplan, 1977;Rehder et al, 1998Rehder et al, , 2002Kessler et al, 2011;Gülzow et al, 2013) and advection of CH 4 -rich freshwaters (Sackett and Brooks, 1975;Cline et al, 1986;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In open oceans, CH 4 sources in shallow water depths are provided by microbial subsurface CH 4 generation taking place in zooplankton guts, the oxygen-deficient interior of particles, or under phosphate-limiting conditions (Karl et al, 2008;Damm et al, 2010). In waters overlying continental shelves, however, the organic-rich sediment serves as a major source of CH 4 in the water column compared to net production in the mixed layer (Martens and Berner, 1974;Martens and Klump, 1980;Reeburgh, 2007). The shallow-water [CH 4 ] can also be elevated due to gas seepages and/or oil spills (Bernard et al, 1976;Reed and Kaplan, 1977;Rehder et al, 1998Rehder et al, , 2002Kessler et al, 2011;Gülzow et al, 2013) and advection of CH 4 -rich freshwaters (Sackett and Brooks, 1975;Cline et al, 1986;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…dissolved SO 4 iil the interstitial waters of recent organic-rich marine sediments indicated that SO4 reduction and CI-I• production are mutually exclusive metabolic processes [Martens and Berner, 1974]. In anoxic incubations with these sediments the ca 4 concentration did not increase until the dissolved SO•4' concentration approached zero [Martens and Berner, 1974 [Bhumbla and Abrol, 1978].…”
mentioning
confidence: 99%
“…In anoxic incubations with these sediments the ca 4 concentration did not increase until the dissolved SO•4' concentration approached zero [Martens and Berner, 1974 [Bhumbla and Abrol, 1978]. For example, in India alone, several million hectares of the Indo-Gangetic plains are alkaline soils on which rice is the major crop in the wet season [Abrol et al, 1985].…”
mentioning
confidence: 99%
“…However, at lower concentrations the rate of reduction appears to be first order (Nakai and Jensen, 1964), although recent studies (Martens and Berner, 1974) claim the reaction is zero order at still lower levels. The rate of sulfate reduction at constant initial sulfate and carbon substrate normalized to a constant bacterial density varies by a factor of 5 between 5° and 25°C (Kaplan and Rittenberg, 1964).…”
Section: Introductionmentioning
confidence: 92%
“…Extreme pressure decreases the rate of sulfate reduction (Jannasch et al, 1971). Measurements of rates of sulfate reduction have utilized the change in concentration with time in laboratorymaintained mud samples (Nakai and Jensen, 1964;Martens and Berner, 1974;Goldhaber and Kaplan, 1975), or by analysis of pore water profiles using mathematical models (Ivanov, 1964). In rich sediments, a month may be required for extensive sulfate removal.…”
Section: Introductionmentioning
confidence: 99%